Sensitivity to hepatotoxicity due to epigallocatechin gallate is affected by genetic background in diversity outbred mice. (February 2015) - Church, Rachel J.; Gatti, Daniel M.; Urban, Thomas J.; Long, Nanye; Yang, Xi; Shi, Qiang; Eaddy, J. Scott; Mosedale, Merrie; Ballard, Shawn; Churchill, Gary A.; Navarro, Victor; Watkins, Paul B.; et al.
Highlights: Diversity Outbred mice modeled rare liver injury that occurs in consumer populations using green tea extract. Genomic investigation of EGCG toxicity in mice identified a candidate quantitative trait locus on chromosome 4. Three genes identified in mice had suggestive association with sensitivity in clinical green tea extract cases. The data indicate that Diversity Outbred mice may be useful for modeling human variability in toxic responses. Abstract: Consumer use of herbal and dietary supplements has recently grown in the United States and, with increased use, reports of rare adverse reactions have emerged. One such supplement is green tea extract, containing the polyphenol epigallocatechin gallate (EGCG), which has been shown to be hepatotoxic at high doses in animal models. The Drug-Induced Liver Injury Network has identified multiple patients who have experienced liver injury ascribed to green tea extract consumption and the relationship to dose has not been straightforward, indicating that differences in sensitivity may contribute to the adverse response in susceptible people. The Diversity Outbred (DO), a genetically heterogeneous mouse population, provides a potential platform for study of interindividual toxicity responses to green tea extract. Within the DO population, an equal exposure to EGCG (50 mg/kg; daily for three days) was found to be tolerated in the majority of mice; however, a small fraction of the animals (16%; 43/272) exhibited severe hepatotoxicity (10–86.8% liver necrosis) that is analogous to the clinical cases. The data indicate that the DO mice may provide a platform for informing risk of rare, adverse reactions that may occur in consumer populations upon ingestion of concentrated herbal products.